2016
DOI: 10.5194/amt-9-3491-2016
|View full text |Cite
|
Sign up to set email alerts
|

Bias corrections of GOSAT SWIR XCO<sub>2</sub> and XCH<sub>4</sub> with TCCON data and their evaluation using aircraft measurement data

Abstract: Abstract. We describe a method for removing systematic biases of column-averaged dry air mole fractions of CO 2 (XCO 2 ) and CH 4 (XCH 4 ) derived from short-wavelength infrared (SWIR) spectra of the Greenhouse gases Observing SATellite (GOSAT). We conduct correlation analyses between the GOSAT biases and simultaneously retrieved auxiliary parameters. We use these correlations to bias correct the GOSAT data, removing these spurious correlations. Data from the Total Carbon Column Observing Network (TC-CON) were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 105 publications
(70 reference statements)
3
32
0
Order By: Relevance
“…The absolute concentrations agree within uncertainties or show no significant difference (Student's t test) at three of the aircraft sites (−1.9 ± 2.2 ppb for RBA, 3.6 ± 4.3 ppb for RBH, 3.6 ± 1.7 ppb for SAN, and 6.6 ± 2.6 ppb for TAB), while the other two show GOSAT to be slightly higher than aircraft measurements, by up to approximately 10 ppb in the most differing case (8.1 ± 2.1 ppb for ALF and 9.7 ± 2.8 ppb for SAH). These results are consistent with results by Inoue et al [, ] who compare GOSAT with aircraft measurements at 17 stations (outside of the Amazon) and find that over land with the same ±5° colocation we use, GOSAT showed a positive station bias of 3.4 ± 7.0 ppb. Uncertainties introduced by the model XCO 2 in the proxy XCH 4 method could account for part of the biases we observe, especially at RBA where the model is shown to be the lowest compared to aircraft measurements.…”
Section: Discussionsupporting
confidence: 92%
“…The absolute concentrations agree within uncertainties or show no significant difference (Student's t test) at three of the aircraft sites (−1.9 ± 2.2 ppb for RBA, 3.6 ± 4.3 ppb for RBH, 3.6 ± 1.7 ppb for SAN, and 6.6 ± 2.6 ppb for TAB), while the other two show GOSAT to be slightly higher than aircraft measurements, by up to approximately 10 ppb in the most differing case (8.1 ± 2.1 ppb for ALF and 9.7 ± 2.8 ppb for SAH). These results are consistent with results by Inoue et al [, ] who compare GOSAT with aircraft measurements at 17 stations (outside of the Amazon) and find that over land with the same ±5° colocation we use, GOSAT showed a positive station bias of 3.4 ± 7.0 ppb. Uncertainties introduced by the model XCO 2 in the proxy XCH 4 method could account for part of the biases we observe, especially at RBA where the model is shown to be the lowest compared to aircraft measurements.…”
Section: Discussionsupporting
confidence: 92%
“…Still further investigation is required in the future. However, the overall mean bias shown here is consistent with the previous results reported by Inoue et al (2014Inoue et al ( , 2016. Inoue et al (2014) made a comparison of GOSAT XCH 4 (V02.00) with 3 aircraft measurements from Yakutsk, Siberia and reported that the bias was 9.2 ± 15.2 ppb (3.7 ± 16.7 ppb) within ±2°( ±5°).…”
Section: Aircraft Xch 4 Comparison With Gosatsupporting
confidence: 91%
“…Inoue et al (2014) made a comparison of GOSAT XCH 4 (V02.00) with 3 aircraft measurements from Yakutsk, Siberia and reported that the bias was 9.2 ± 15.2 ppb (3.7 ± 16.7 ppb) within ±2°( ±5°). When considering 2 days average excluding a date of October 05, 2014, we obtained a bias 3.47 ± 1.51 ppb, which is agreed with Inoue et al (2016) who showed a 4.5 ± 15. 20 ppb over land.…”
Section: Aircraft Xch 4 Comparison With Gosatsupporting
confidence: 91%
“…Satelliteinferred XCH 4 observations are increasingly used in atmospheric inverse modeling because of their beneficial spatiotemporal data coverage (Bergamaschi et al, 2013;Fraser et al, 2013Fraser et al, , 2014Monteil et al, 2013;Houweling et al, 2014;Wecht et al, 2014;Cressot et al, 2014;Alexe et al, 2015;Turner et al, 2015;Locatelli et al, 2015). Given the high accuracy of ground-based XCH 4 TCCON retrievals, these observations are typically used for the evaluation of both chemistry-transport model (CTM) simulations (Saito et al, 2012;Belikov et al, 2013;Monteil et al, 2013;Alexe et al, 2015;Turner et al, 2015) and satelliteretrieved XCH 4 (Parker et al, 2011Schepers et al, 2012;Dils et al, 2014;Houweling et al, 2014;Parker et al, 2015;Kulawik et al, 2016;Pandey et al, 2016;Inoue et al, 2016).…”
Section: Introductionmentioning
confidence: 99%